Correlation between serum vitamin D levels and handgrip strength in prepubertal children - Arokiaraj, Anand (Journal of Neonatal Surgery, 2025)
Background:Vitamin D plays a critical role in musculoskeletal health, with emerging evidence suggesting a relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and muscle strength. However, limited data exist for healthy prepubertal children. Methods:A cross-sectional study was conducted among 110 healthy children aged 5–10 years recruited from urban primary schools. Anthropometric data, physical activity, and sun exposure were recorded. Serum 25(OH)D was measured via chemiluminescent immunoassay. Handgrip strength was assessed using a calibrated dynamometer following standardized protocols. Correlation and multiple linear regression analyses were performed, adjusting for age, sex, BMI, and physical activity. Results:The mean serum 25(OH)D concentration was 60.2 ± 15.1 nmol/L, and the mean handgrip strength was 11.2 ± 2.1 kg. Serum 25(OH)D showed a moderate positive correlation with handgrip strength (r = 0.32, p < 0.01). In multivariable analysis, vitamin D remained a significant predictor (β = 0.05, 95% CI: 0.02–0.08, p < 0.01), along with age and physical activity. Sex-stratified analysis revealed stronger correlation in males (r = 0.55) than in females (r = 0.28). Conclusion:Higher serum 25(OH)D levels were significantly associated with greater handgrip strength in healthy prepubertal children, particularly in males. These findings highlight the importance of maintaining adequate vitamin D status and promoting active lifestyles to support pediatric musculoskeletal health